Southwest Asia : the Transpacific geographies of Chicana/o literature - Sae-Saue, Jayson Gonzales (New Brunswick, New Jersey : Rutgers University Press, 2016)
Southwest Asia investigates why key Chicana/o writers, from the 1950s to the present day, have persistently referenced Asian people and places in the course of articulating their political ideas. Raising concerns about how these texts invariably marginalize their Asian characters and suggesting that darker legacies of imperialism and exclusion might lurk beneath their utopian visions of a Chicana/o nation, Jayson Gonzales Sae-Saue takes our conception of Chicana/o literature as a transnational movement in a new direction.
Introduction: The promise and problem of interracial politics for Chicana/o culture -- Racial equivalence and the transpacific geographies of Chicana/o nationalism in Vietnam Campesino, the revolt of the cockroach people, and pilgrims in Aztlán -- Forging and forgetting transpacific identities in Américo Paredes's "Ichiro Kikuchi" and Rolando Hinojosa's Korean love songs -- Conquest and desire: interracial sex in Daniel Cano's shifting loyalties and Alfredo Véa's Gods go begging -- Through Mexico and into Asia: a search for cultural origins in Rudolfo Anaya's A Chicano in China -- Chinese immigration, mixed-race families, and China-cana feminisms in Virginia Grise's Rasgos Asiáticos -- Coda: Chicano studies then and now: paradigms of past and future critique.
Includes bibliographical references (pages 157-169) and index.
Print version record.
English.
JSTOR
Keywords: American literature -- Mexican American authors -- History and criticism; Mexican Americans -- Asia; Internationalism in literature; Littérature américaine -- Auteurs américains d'origine mexicaine -- Histoire et critique; Américains d'origine mexicaine -- Asie; Internationalisme dans la littérature.; LITERARY CRITICISM -- American -- General; LITERARY CRITICISM -- American -- Asian American; American literature -- Mexican American authors; Internationalism in literature; Mexican Americans; Asia; Criticism, interpretation, etc